The nutty professor [videorecording (DVD)] - Lewis, Jerry, 1926-2017; Richmond, Bill; Stevens, Stella, 1936-; Moore, Del, 1916-1970; Freeman, Kathleen, 1919-2001; Flory, Med, 1926-2014; Alden, Norm, 1924-2012; Morris, Howard, 1919-2005; Allman, Elvia; Frome, Milton; Gibson, Henry; Brown, Les, 1912-2001 (Widescreen collection, 2004)
To improve his social life, a nerdish professor drinks a potion that temporarily turns him into the handsome, but obnoxious, Buddy Love.